2018
DOI: 10.7567/jjap.57.08rb07
|View full text |Cite
|
Sign up to set email alerts
|

Dense restructuring of amorphous silicon network induced by non-bonded hydrogen

Abstract: We confirmed the presence of non-bonded hydrogens (NBHs) in hydrogenated amorphous silicon (a-Si:H) films, using a combination of multiple techniques (Rutherford backscattering spectrometry/hydrogen forward scattering, Fourier-transform infrared spectroscopy-attenuated total reflection, and thermal desorption spectrometry). The hydrogen effusion profile of an a-Si:H film with large amounts of NBHs was analyzed in detail. We report the effect of NBHs on band structure and electrical conductivity, and we present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 87 publications
(222 reference statements)
5
10
0
Order By: Relevance
“…This parameter is associated with the atomic coordinance average number, so its decrease suggests more vacancies are introduced in the tissue . This result agrees with the findings reported by Sekimoto et al, which revealed the aggregation of vacancies driven by the hydrogen molecules trapped within …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This parameter is associated with the atomic coordinance average number, so its decrease suggests more vacancies are introduced in the tissue . This result agrees with the findings reported by Sekimoto et al, which revealed the aggregation of vacancies driven by the hydrogen molecules trapped within …”
Section: Discussionsupporting
confidence: 92%
“…This porosity seems to increase further, as the static index decreases to around 2.7, as a result of the H 2 treatment, in agreement with the ellipsometry results. This result is in line with the suggestion that hydrogen molecules in the film lead to the creation of nanovoids, as proposed in the study of Sekimoto et al and Sekimoto, Matsumoto, and Terakawa . Moreover, E w is decreased from 27 to 21 eV.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Experimental data from positron-annihilation lifetime (PAL) spectroscopy, 13 Rutherford backscattering spectrometry (RBS), 59 and Fourier-transform infrared spectroscopy-attenuated total reflection (FTIR-ATR) 59 This value matches very well with the experimental value of 10 21 H 2 /cm 3 from IR measurements by Chabal and Patel, 24 as mentioned earlier. These results are also consistent with the reported data from RBS measurements.…”
Section: Silicon-hydrogen Bonding Configurations On Void Surfacessupporting
confidence: 75%